Magnesium, calcium and zinc [N2N'] heteroscorpionate complexes - Luna Barros, M; Cushion, M; Schwarz, A; Turner, Z; Mountford, P (Royal Society of Chemistry, 2019)
A new family of sterically demanding N2N′ heteroscorpionate pro-ligands (HC(tBu2pz)2SiMe2N(H)R (R = iPr, tBu, Ph, Xyl)) has been prepared via a straightforward modular synthetic route. An extensive study into the synthesis and characterisation of lithium, magnesium, calcium and zinc complexes supported by both 3,5-tBu and 3,5-Me substituted N2N′ ligand families has been conducted. Attempted deprotonation of the pro-ligands with nBuLi afforded the corresponding lithium salts Li{HC(tBu2pz)2SiMe2NR} (R = iPr (1), tBu (2), Ph (3) and Xyl (4)) but air- and thermal-sensitivity limited the yields of these potentially useful precursors; only the sterically encumbered ligand system allowed clean reactivity. Magnesium methyl complexes Mg{HC(tBu2pz)2SiMe2NR}Me (R = iPr (5) and R = Ph (6)) were prepared using an excess of the Grignard reagent MeMgCl. Magnesium butyl complexes were synthesised in good yields using the dialkyl precursor MgnBu2 to afford Mg{HC(R′2pz)2SiMe2NR}nBu (R′ = Me; R = iPr (7), tBu (8), Ad (9), Ph (10). R′ = tBu; R = iPr (11), Ph (12)). Protonolylsis reactions were used to synthesise magnesium and calcium amide complexes Mg{HC(R′2pz)2SiMe2NR}{N(SiHMe2)2} (R′ = Me; R = iPr (13), tBu (14), Ph (15). R′ = tBu; R = Ph (16)) or Mg{HC(R′2pz)2SiMe2NR}{N(SiMe3)2} (R′ = Me; R = iPr (17), tBu (18), Ph (19). R′ = tBu; R = Ph (20)), and Ca{HC(R′2pz)2SiMe2NR}{N(SiMe2)2} (L) (R′ = Me; L = thf; R = iPr (21), tBu (22), Ph (23). R′ = tBu; L = none; R = Ph (24). Zinc methyl complexes Zn{HC(R′2pz)2SiMe2NR}Me (R′ = Me; R = iPr (25), tBu (26), Ph (27). R′ = tBu; R = Ph (28)) were prepared by reaction of the N2N′ heteroscorpionate pro-ligands with ZnMe2. In preliminary studies, magnesium amide complexes 16 and 20 were evaluated as initiators for the ring-opening polymerisation (ROP) of ε-caprolactone (ε-CL) and rac-lactide (rac-LA). Although the overall polymerisation control was poor, 16 and 20 were found to be active initiators.